Women and Climatic Changes in Ethiopia: A Gendered Assessment - (:unkn) unknown (My University, 2016)
Within the broader issue of climate changes, the current discourse seeks to prioritize adaptation measures in tackling the adverse effects of global warming rather than a reliance only on mitigation efforts (Aguilar, 2009; UNFCCC, 2010). In this process, women are given an increasing role to play, as the gender approach has shown its enhanced potential in creating sustainable development. Indeed, on June 26th 2014, at Malabo (Equatorial Guinea), the Committee of African Heads of State and Government resolved to develop a “Women and Gender Program on Climate Change”. However, behind the motives of this new approach are the same familiar challenges to be met, the same reports on the position of women within the society, the important role of women in situations of poverty, their low educational level, their difficulty in getting access to information and financial credit or in being included in decisions at political, community and family levels. We must wonder about the intrusion of the question of gender within consideration of the need for adaptation to climate change, which is a part of a wider movement linked with development aid in general. The public and private funding assigned to the resolution of this worldwide danger raises the questions of opportunism, financial confusion and/or lack of general consideration towards the actors involved in the promotion of gender equality. But we shall also take the opportunity to measure the transformations this all implies for the Ethiopian associations that advocate improvement of women’s conditions. Finally, can the theme “Gender and Climate” in Ethiopia propose new paradigms for reflection?The aim of this paper is therefore to understand how women have been recognized as effective and independent actors in answering some of the challenges posed by climate change. At the same time, we want to question the relevance and reliability of a gendered approach in overcoming the problems generated by cli
Keywords: African Research